Rendering the Qur'an into Cadenced, Rhyming English Prose: Process and Outcome in a Translation of Sūrat al-Ghāshiya (Q. 88). Issue 2 (June 2015) - Toorawa, Shawkat M.
<x xml:space="preserve">Abstract</x> Translators of the Qur'an often explain the general principles underlying their translation but rarely, if ever, go into the nitty-gritty of the process and discuss aspects such as specific word choice, word placement, rhyme/non-rhyme, assonance/consonance, and so on. Either they do not think about these dimensions of their translation explicitly, or soundscape and soundshape is not as important to them as 'meaning'. As a translator who believes that Qur'anic meaning inheres in word placement and word choice, I aim to demonstrate how this can be transferred to the English translation by recording all my choices as I translated Sūrat al-Ghāshiya (Q. 88). Thus, process (the act of translation) is made explicit, and product (translation proper) can be appreciated as the outcome of the process. Another important aim of this discussion is to encourage others translating the Qur'anic text (from single verses for quotation in their own scholarship to longer pieces or, indeed, the whole Qur'an) to appreciate the importance of word placement and choice, even in the target language (in this case, English).